The trade dependence of Mexico and Canada towards the USA: An input-output approach (1965-1990) - Romero-Ramírez, Héctor (Estudios Económicos de El Colegio de México, 2023)
This paper studies the integration of Canada and Mexico with the United States of America (USA) prior to the North American Free Trade Agreement. Input-Output techniques were used, and it was found that Canada and Mexico were integrated with the USA but with different characteristics. Since most Canadian industries with greater integration are not linked to the automotive industry, these results are curious because, during practically the entire period, the free trade agreement in force was that of the automotive industry. Among the most integrated Mexican industries are some associated with maquiladoras, which suggests a concordance between Mexico's policies and its integration with the USA.